2004
DOI: 10.1111/j.1440-1789.2004.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin‐like growth factors in remyelination following ethidium bromide‐induced demyelination in the mouse spinal cord

Abstract: Insulin-like growth factors, IGF-I and IGF-II, play important roles in development and myelination in the CNS, but little is known about the response of IGF after demyelination. The present study investigated the expression of IGF and their cognitive receptors in the process of remyelination following ethidium bromide (EBr)-induced demyelination in the adult mouse spinal cord. The present results, in a quantitative real-time PCR, showed significant increases in the levels of the mRNA for both IGF-I and IGF-II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…IGF-I, produced locally or delivered to the CNS from the circulation, induces a constitutive level of IGF1R-mediated signalling in the adult CNS, which is important for brain functions and adult neurogenesis [68]. This level can increase in response to a pathological process in the CNS [69] or as a result of adaptive response to exercise and correlates with increased hippocampal neurogenesis [70]. Secretion of IGF1R ligands in organising centres or its expression in a graded manner is not characteristic for the developing mammalian CNS whose patterning, by contrast to the neurogenesis in Xenopus laevis [71][72][73], is not known to depend on IGF1R activation.…”
Section: Igf1r In Neurogenesismentioning
confidence: 99%
“…IGF-I, produced locally or delivered to the CNS from the circulation, induces a constitutive level of IGF1R-mediated signalling in the adult CNS, which is important for brain functions and adult neurogenesis [68]. This level can increase in response to a pathological process in the CNS [69] or as a result of adaptive response to exercise and correlates with increased hippocampal neurogenesis [70]. Secretion of IGF1R ligands in organising centres or its expression in a graded manner is not characteristic for the developing mammalian CNS whose patterning, by contrast to the neurogenesis in Xenopus laevis [71][72][73], is not known to depend on IGF1R activation.…”
Section: Igf1r In Neurogenesismentioning
confidence: 99%
“…In the developing white matter, AMC have also been reported to function as guides for developing axons, perhaps through the manufacture of extracellular matrix molecules, such as thrombospondin [49,50] . Insulin-like growth factors Insulin-like growth factor (IGF) I and II are known to regulate the development of the nervous system [51] . IGF-I plays an important role in promoting cell proliferation and differentiation [52] in the devel-oping brain.…”
Section: Nature Of Amcmentioning
confidence: 99%
“…Several studies have shown a role of antibodies against MOG in the pathogenesis of MS [10]. Growth factors including insulin like growth factor were shown to be important in repair processes of demyelination [12]. Ciliary neurotrophic factor (CNTF) and leukemia inhibitory factor (LIF) have been shown to have an important role in the process of remyelination by increasing Opalin (34 KDa) and MOG expression [23,29].…”
Section: Discussionmentioning
confidence: 99%